Bioassay-guided Isolation of Constituents of Piper sarmentosum Using a Mitochondrial Transmembrane Potential Assay - Pan, Li (2011)
Bioassay-guided fractionation was conducted on a chloroform-soluble extract of the aerial parts of Piper sarmentosum collected in Vietnam, monitored by a mitochondrial transmembrane potential (MTP) assay using HT-29 human colon cancer cells. This led to the isolation of four new C-benzylated dihydroflavones, sarmentosumins A-D (1-4), as well as 14 known compounds. The structures of the new compounds were elucidated on the basis of spectroscopic data interpretation. Among these compounds, 1-4 as well as five known C-benzylated dihydroflavones (5-9), and pipercallosine, a piperamide (11), were found to induce apoptosis in HT-29 cells by moderately reducing the mitochondrial transmembrane potential (ΔΨm), with ED(50) values ranging from 1.6 to 13.6 μM. Furthermore, 7-methoxydichamanetin (8) and pinocembrin (10) exhibited proteasome inhibitory activities in a human 20S proteasome bioassay with IC(50) values of 3.45 ± 0.18 μM and 2.87 ± 0.26 μM, respectively. This is the first time that C-benzylated dihydroflavones have been reported to demonstrate an apoptotic effect associated with disruption of the mitochondrial transmembrane potential.